Support Vector Machine Ensemble Based on Feature and Hyperparameter Variation. - WANDEKOKEN, E. D. (2016)
Made available in DSpace on 2016-08-29T15:33:14Z (GMT). No. of bitstreams: 1 tese_4163_.pdf: 479699 bytes, checksum: 04f01a137084c0859b4494de6db8b3ac (MD5) Previous issue date: 2011-02-23